Analysis of Competitiveness and Determinants of Indonesia Palm Oil Export - Rozi, Muhammad Fahrur; Atmanti, Hastarini Dwi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Indonesia is the largest palm oil producing country in the world along with Malaysia, but in 2024 Indonesia's total oil exports will decline. The reason for choosing palm oil exports is because Indonesia's largest export commodity is palm oil, the method used is the revealed comparative advantage index to measure comparative advantage and the gravity model to measure factors that influence exports, the results show that Indonesia has a comparative advantage for trading partner countries, then Indonesia's GDP has a positive but insignificant effect on palm oil exports, the GDP of trading partner countries has a negative but insignificant effect, the exchange rate has a negative but insignificant effect on palm oil export, population significantly effect on palm oil exports and economic distance has a negative but insignificant effect on palm oil export.